The 2010 International Joint Conference on Neural Networks (IJCNN) 2010
DOI: 10.1109/ijcnn.2010.5596644
|View full text |Cite
|
Sign up to set email alerts
|

Neural network-based taxonomic clustering for metagenomics

Abstract: Abstract-Metagenomic studies inherently involve sampling genetic information from an environment potentially containing thousands of distinctly different microbial organisms. This genetic information is sequenced producing many short fragments (<500 base pair (bp)); each is tentatively a small representative of the DNA coding structure. Any of the fragments may belong to any of the organisms in the sample, but the relationship is unknown a priori. Furthermore, most of these organisms have not been identified a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…One of the first techniques of de novo genome binning used self-organizing maps, a type of neural network [311]. Essinger et al [331] used Adaptive Resonance Theory to cluster similar genomic fragments and showed that it had better performance than k-means. However, other methods based on interpolated Markov models [332] have performed better than these early genome binners.…”
Section: Metagenomicsmentioning
confidence: 99%
“…One of the first techniques of de novo genome binning used self-organizing maps, a type of neural network [311]. Essinger et al [331] used Adaptive Resonance Theory to cluster similar genomic fragments and showed that it had better performance than k-means. However, other methods based on interpolated Markov models [332] have performed better than these early genome binners.…”
Section: Metagenomicsmentioning
confidence: 99%
“…The one-hot encoding of a sequence is a limited method with respect to the goal of grouping it with others (binning). Various methods perform binning using autoencoders but relying on one-hot encoding [ 102 103 ] or reference database annotations only [ 104 ]. However, these methods are now outperformed by methods that provide better sequence representations.…”
Section: Resultsmentioning
confidence: 99%
“…This vector is then projected into a latent space, thereby producing a novel data visualization. These points can be grouped through clustering algorithms such as k-medoids or k-means based on their proximity in the embedding space [ 104 108 ]. These groups and their population will form the abundance table.…”
Section: Resultsmentioning
confidence: 99%
“…The latent representations of all sequences constitute a spatial distribution of the data, with each point representing an individual sequence. These points can be grouped through clustering algorithms such as k-medoids or k-means ( [84] [80]). Once clustered, these sequences aggregate into groups representing their proximity in the embedding space, and therefore hopefully their real proximity.…”
Section: Classification Of Reads Computing An Abundance Matrix By Gro...mentioning
confidence: 99%